Design and Manufacturing of Integrated Drilling and Cutting Orthopedic Bone-Specific Surgical Guide. Issue 5 (3rd April 2016) - Ebrahimzadeh, Ali; Azimifar, Farhad; Nosouhi, Reza
Abstract : In this paper, the design and fabrication of a bone-specific double function surgical guide are presented. The design of this surgical guide is performed so that it can be used simultaneously for drilling and cutting of cow's tibia bone. The employment of this surgical guide results in higher accuracy, reduction of the number of the holes needed to be pierced through the bone, and lower surgery time. The research is performed in three steps including the digitizing of the bone and production of the bone's 3D model in CATIA (generative shape design environment), design of surgical guide, and fabrication of the guide by FDM process. The guide is used for drilling and cutting of the bone.